Building Early Childhood Collaboration through Cultural Projects: A Descriptive Study in a Local Learning Context - Atika Putri, Azlin; M. Syarif Sumantri; Hapidin (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
A 21st-century skill that must be taught from a young age is collaboration. This skill emphasizes social values, empathy, and shared responsibility in the context of early childhood education. It also includes group cooperation. The purpose of this study is to explain how a cultural project based on local knowledge from Riau Malay might encourage cooperation among young children in a kindergarten setting. The research employed a descriptive design and a qualitative methodology. Teachers and students at a kindergarten in Pekanbaru who used the cultural initiative in their lesson plans made up the research subjects. Participatory observation, in-depth interviews, and documentation were used to gather data, which were subsequently subjected to data reduction, data presentation, and conclusion drawing methodologies for analysis. The findings demonstrated that children's empathy, shared responsibility, and positive social connections may be fostered through local culture-based activities like folktale performances, traditional games, and the creation of regional musical instruments. Teachers served as facilitators, directing group dynamics and incorporating cultural values from the area into the educational process. These results attest to the effectiveness of the local wisdom-based cultural initiative in fostering early childhood teamwork and promoting the preservation of Riau Malay culture.